Fundamentals of corporate finance - Brealey, Richard A. (McGraw-Hill, 1995)
Brealey, Myers, Marcus were applauded for their intuitive approach and imbedded examples. Professors constantly praised their well-organized and thoughtful writing style and their clear exposition of what many students consider difficult material. The authors accomplished this without sacrificing an up-to-date, technically correct treatment of core topic areas.